2008
DOI: 10.4049/jimmunol.180.3.1758
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Human Subjects Have CD4+ T Cells Directed against H5N1 Influenza Virus

Abstract: It is commonly perceived that the human immune system is naive to the newly emerged H5N1 virus. In contrast, most adults have been exposed to influenza A H1N1 and H3N2 viruses through vaccination or infection. Adults born before 1968 have likely been exposed to H2N2 viruses. We hypothesized that CD4+ T cells generated in response to H1N1, H3N2, and H2N2 influenza A viruses also recognize H5N1 epitopes. Tetramer-guided epitope mapping and Ag-specific class II tetramers were used to identify H5N1-specific T cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
109
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(112 citation statements)
references
References 31 publications
2
109
0
1
Order By: Relevance
“…Humans who have not been exposed to avian influenza A (H5N1) virus do have crossreactive memory CD4 and CD8 T cells to a wide range of H5N1 peptides (33,47). More recently, one study also showed that some seasonal influenza A virus-specific memory T cells in individuals without exposure to prior pdmH1N1 infection can recognize pdmH1N1 (24).…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…Humans who have not been exposed to avian influenza A (H5N1) virus do have crossreactive memory CD4 and CD8 T cells to a wide range of H5N1 peptides (33,47). More recently, one study also showed that some seasonal influenza A virus-specific memory T cells in individuals without exposure to prior pdmH1N1 infection can recognize pdmH1N1 (24).…”
mentioning
confidence: 87%
“…Most importantly, the cross-protection of such CTLs has been demonstrated in humans in vivo by the Cleveland family study, in which persons who had experienced symptomatic H1N1 influenza were found to be partially protected from the following pandemic H2N2 virus infection in 1957 (17,46). Indeed, even for adults over 60 years old, the cross-reactive T-cell responses play some role despite the fact that they have some level of preexisting antibodies, as the cellular responses, but not antibodies, are cor- It is interesting that the disease severity seems not to be related to the preexisting cross-reactive memory T cells during infection with the highly pathogenic avian influenza virus, although cross-reactive memory T cells have been detected in healthy populations by determining the IFN-␥ responses (29,32,33,47). The fact that lethal H5N1 influenza viruses are resistant to the antiviral effects of IFN-␣, IFN-␥, or TNF-␣ may partially explain this (49).…”
Section: Cross-response Of Bulk Ctls Against Pdmh1n1 In Healthy Indivmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously shown that vaccination of young subjects with inactivated influenza vaccine slightly enhanced the total CD4 +  CD45RO + memory T cells, but the proportion of people with such increases was <20% 11 . Stimulation of total memory T cells seems to be associated with the phenomenon of polyclonal activation of heterotypic lymphocyte subpopulations specific to other antigens (bystander activation) 27 , 28 , 29 . The LAIV FluMist (MedImmune, Gaithersburg, MD, USA) was shown to be able to stimulate influenza‐specific IFNγ‐producing CD4 T cells 12 , 30 .…”
Section: Discussionmentioning
confidence: 99%
“…For ubiquitous viruses such as influenza, flu-specific memory T cells have been detected in the peripheral blood and lungs of healthy individuals (17,18). In particular, influenza-specific memory CD4 T cells generated from exposure to seasonal strains were found to cross-react with avian influenza (H5N1) epitopes (19,20). These results suggest that memory CD4 T cells could form a "first-line" defense in responses to new or variant influenza strains that evade neutralizing Ab responses; however, the ability of memory CD4 T cells to direct secondary responses to influenza has not been defined.…”
mentioning
confidence: 99%